2005
DOI: 10.1088/0031-9155/50/24/006
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of output factors for spread-out proton Bragg peak fields in clinical practice

Abstract: The reliable prediction of output factors for spread-out proton Bragg peak (SOBP) fields in clinical practice remained unrealized due to a lack of a consistent theoretical framework and the great number of variables introduced by the mechanical devices necessary for the production of such fields. These limitations necessitated an almost exclusive reliance on manual calibration for individual fields and empirical, ad hoc, models. We recently reported on a theoretical framework for the prediction of output facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 13 publications
(14 reference statements)
1
55
0
Order By: Relevance
“…At our institution, a theoretical model, based on the observation that the OF is the ratio of the SOBP plateau dose to the dose measured in the reference chamber IC2, is clinically used to predict the OF and for their constancy verification for any specific SOBP. 22 Output factors are measured routinely within the QA program for each option reported in Table I.…”
Section: B2 Output Factors Measurements and Simulations For Absolmentioning
confidence: 99%
“…At our institution, a theoretical model, based on the observation that the OF is the ratio of the SOBP plateau dose to the dose measured in the reference chamber IC2, is clinically used to predict the OF and for their constancy verification for any specific SOBP. 22 Output factors are measured routinely within the QA program for each option reported in Table I.…”
Section: B2 Output Factors Measurements and Simulations For Absolmentioning
confidence: 99%
“…8 Our reference geometry uses no range compensator as advocated by Kooy et al 3 and Fontenot et al 4 Range:…”
Section: Iib Standardized Setup For Commissioningmentioning
confidence: 99%
“…Although a standard for determining the in-patient output of a passivescattered proton field has not yet been developed, the current consensus in the proton therapy community is to perform field calibrations without the use of a range compensator. Kooy et al 3 reported on relying on the treatment planning system to calculate the effect of the range compensator and in-patient scatter, and therefore not to use field specific hardware during field calibrations. Monte Carlo data by Fontenot et al 4 supports this change.…”
Section: Iva Limitations Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…For DMU calculations, Kooy et al 2 , 3 developed a semi‐empirical calculation method for a range modulated proton beam. It is based on the fact that the DMU depends on the ratio of the entrance dose and the reference dose.…”
Section: Introductionmentioning
confidence: 99%